‘‘Why She Disappeared’’ (A Study of Illeism in Poetic Discourse) - Alek Alek; Abdul Gafur Marzuki; Didin Nuruddin Hidayat; Farhana Amalya Islamiati; Aning Rustanti Raharjo (Universitas Cokroaminoto Palopo, 2020)
The paper in hand is an attempt to apply discourse analysis approach to analyze the use of illeism in poetic eloquence. Illeism is used in third-person self-reference forms for representing the views of someone else as distinctive technique of interpretation. Through this means, it creates illusion of the speaker linguistically and thematically trying to distance themselves in the narrative. The paper is an analysis of Taylor Swift’s poem “Why She Disappeared” for her sixth studio album ‘Reputation’. The study explores qualitatively poetry elements in accordance to highlight the implication of illeism through signifiers. It utilizes a literary approach and the poem as the corpus of the study. The aims of the study are to address the way illeism functioning within the poem and the interpretation of the third-person self-reference in the poem. It is found that the poem presents the use of illeism in threefold: (1) it is used to distance oneself from traumatic occurrences; (2) it is used to refer to past-self indirectly; (3) it is used to give self-motivation. The third-person terms mentioned in the poem contribute to the actions that the speaker is employing through the discourse. Further study is needed to explore more about illeism in a variety of discourse.